Controls on geothermal heat recovery from a hot sedimentary aquifer in Guardbridge, Scotland: Field measurements, modelling and long term sustainability. (November 2018) - Comerford, A.; Fraser-Harris, A.; Johnson, G.; McDermott, C.I.
Highlights: Fault architecture determined from detailed field fracture mapping. DFN modelling of potential HSA in fault damage zone of regional scale fault. First 3D thermo-hydraulic coupled numerical model of potential site at Guardbridge. Potential renewable heat production for >50 years supplying c. 11% of local demand. Abstract: Geothermal heat from Hot Sedimentary Aquifers represents a promising intermediate (30°C) resource for district heating systems. A key control on the geothermal productivity of these aquifers is the architecture of faults, which can significantly enhance or reduce the natural permeability of these systems. We present the first three-dimensional coupled groundwater flow and heat transport numerical model, combining multiple data from field mapping and fracture surveys, of two intersecting major fault systems in Central-East Scotland. This includes fault-zone fracture permeability modelling, depth-dependent permeability modelling, geo-mechanical facies assessment and heat productivity estimates for single well and multiple well extraction scenarios. Simulations indicate that with careful location of extraction wells within permeable fault systems, production is sustainable for over 50 years for multiple-well extraction scenarios in this region.